Advancements in research on high-overload impact-buffering protective materials - Zhang, An; Liu, Peng; Zhang, He (Frontiers in Mechanical Engineering, 2024)
The penetration fuze, as the initiation control component of the penetration weapon, usually experiences an overload of tens of thousands or even hundreds of thousands of g during the penetration process.In order to prevent the fuze from being overloaded and causing the weapon to explode or misfire early, this article introduces the use of internal sealing reinforcement and external energy absorbing buffer materials to protect the internal circuit modules of the fuze.Several kinds of energy absorbing and buffering materials, including foam metal materials and composite sandwich structure materials, as well as metamaterials that have recently attracted the attention of industry and academia, are reviewed. The high overload impact energy absorption characteristics of materials and the mechanical properties of different material structures are emphatically introduced.In addition, this article also evaluates the applicability and limitations of existing buffer materials and methods, and proposes some potential improvement plans, such as the impact of parameters such as viscoelasticity, porosity, surface coating, printing process, heat treatment process on the energy absorption effect of materials, further improving the engineering practicality of buffer protection materials. A summary of the key technologies in the research of penetration fuze protective materials was made, and some mechanical testing methods were proposed, which can better characterize the impact resistance and resilience of materials. Finally, the future development direction of buffer materials for penetration fuzes was explored, which will help promote the research on the concept of buffer materials used on penetration missiles.